Identifying Gaps and Missed Opportunities for Intravenous Thrombolytic Treatment of Inpatient Stroke - Topiwala, Karan; Tarasaria, Karan; Staff, Ilene; Beland, Dawn; Schuyler, Erica; Nouh, Amre (Frontiers in Neurology, 2020)
Background: Inpatient stroke-codes (ISC) have traditionally seen low treatment rates with IV-thrombolytic (IVT). The purpose of this study was to identify the predictors of true stroke, prevalent IVT-treatment gap and study the factors associated with such missed treatment opportunities (MTO). Methods: A retrospective chart review identified ISC from March 2017 to March 2018. Clinical, radiographic and demographic data were collected. Primary analysis was performed between stroke vs. non-stroke diagnoses. Dichotomous variables were analyzed using Chi-Square test of proportions and continuous variables with Wilcoxon-Ranked-Sum test. Significant factors were then tested in a multivariate logistic regression model for independence. Results: From 211 ISC, 36%(n=76) had an acute stroke. Hemorrhagic stroke (HS) was present in 5.7%(n=12). Of the remaining 199, 44%(n=87) were IVT-eligible but only 3.4%(n=3) were treated. Of the remaining 84 IVT-eligible-but-untreated patients, 69(82.1%) were mimics, while 15(17.9%) had an ischemic stroke (IS), constituting a MTO of 1 in 6 IVT-eligible patients, with National Institutes of Health Stroke Scale (NIHSS) ≤4 being the commonest deterrent. Independent predictors of stroke were ejection fraction (EF) <30% (p=0.030, OR 3.06), post-operative status (p=0.001, OR 3.71), visual field-cut (p=0.008, OR 3.70) and facial droop (p=0.010, OR 2.59). Conclusion: In our study, one in three ISC were true strokes. IVT treatment rates were low with a MTO of 1 in 6 IVT-eligible patients. The most common reason for not treating was NIHSS ≤4. Knowing predictors of true stroke and the common barriers to IVT treatment can help narrow this treatment gap.